2017
DOI: 10.1007/jhep11(2017)068
|View full text |Cite
|
Sign up to set email alerts
|

The transverse momentum distribution of hadrons within jets

Abstract: We study the transverse momentum distribution of hadrons within jets, where the transverse momentum is defined with respect to the standard jet axis. We consider the case where the jet substructure measurement is performed for an inclusive jet sample pp → jet + X. We demonstrate that this observable provides new opportunities to study transverse momentum dependent fragmentation functions (TMDFFs) which are currently poorly constrained from data, especially for gluons. The factorization of the cross section is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
106
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(107 citation statements)
references
References 121 publications
(193 reference statements)
1
106
0
Order By: Relevance
“…The size of any such factorization breaking is not known. It has recently been argued that the cross section for hadrons within jets produced from proton-proton collisions does factorize and only depends upon universal TMD fragmentation functions, decoupled from TMD PDFs [29]. It has also been shown that as the value of the soft TMD scale becomes larger, the twist-3 and TMD approaches are mutually consistent [30].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…The size of any such factorization breaking is not known. It has recently been argued that the cross section for hadrons within jets produced from proton-proton collisions does factorize and only depends upon universal TMD fragmentation functions, decoupled from TMD PDFs [29]. It has also been shown that as the value of the soft TMD scale becomes larger, the twist-3 and TMD approaches are mutually consistent [30].…”
Section: Introductionmentioning
confidence: 95%
“…These pions are required to have 0.1 < z < 0.8, where z is the ratio of pion momentum to jet momentum (note that this definition for z is referred to as z h in Ref. [29]). A significant portion of pions with z < 0.1 in low p T jets arises from underlying event backgrounds, while z ¼ 0.8 marks the limit for sufficient statistics in this data set.…”
Section: E Pion Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…For alternative definitions of similar observables see Refs. [21,22]. The operator definition of TMD-FJF is the following,…”
Section: Transverse Momentum Dependent Fragmenting Jet Functionsmentioning
confidence: 99%
“…The size of any such factorization breaking is not known. It has recently been argued that the cross section for hadrons within jets produced in p + p does factorize and only depends upon universal TMD fragmentation functions, decoupled from TMD PDFs [10]. In contrast to TMDs, IFF asymmetries persist in the collinear framework of pQCD, where factorization and universality are expected to hold [11].…”
Section: Introductionmentioning
confidence: 99%